A Class of Its Own : Re-Envisioning American Labor Fiction. - Hapke, Laura; Kirby, Lisa A. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2008)
A Class of Its Own positions important and rediscovered American social protest authors Otherin both a scholarly and student-centered context. The volume draws on the expertise and pedagogy of established and younger scholars who move gracefully from theories of what makes a text "working class" to how studies of class empower college teachers and courses. Among the authors discussed in the volume's essays and prominent in the book's syllabi section are Zora Neale Hurston, Stephen Crane, Agnes ...
Embattled radicals : difficulties and models -- Reading "Red" : the working-class novel comes of age -- Modern occasions : the multi-ethnic heritage of working-class fiction --Class in the classroom : a variety of approaches.
Print version record.
Includes bibliographical references.
eBooks on EBSCOhost
Keywords: American fiction; Working class writings, American; Working class in literature; Roman américain.; Écrits d'ouvriers américains.; Travailleurs dans la littérature.; LITERARY CRITICISM -- American -- General; American fiction; Working class in literature; Working class writings, American